(untitled) - Schmitt, Thomas (Hoboken, N.J., 2007)
Despite the seemingly endless challenges and pressures in today's workplace, many people are firm in their resolve to assume leadership roles and make a difference. The problem? There simply isn't a clear-cut path to follow.
Keywords: Leadership,Simplicity,Problem solving,Employee motivation,Lãnh đạo,Sự đơn giản,Giải quyết vấn đề,Sự trình bày của nhân viên